Pengaruh Trend Investasi Dalam Perkembangan Pasar Modal Syariah - Fadlie, Rivaldo Adiwijaya Aji (PT Literasi Nusantara Publisher, 2024)
This study aims to see how much influence the trend of investing in the past few years has on the developmentt of the capital market, especially the Islamic capital market. This research is expected to have benefits for readers or investors (stakeholders) in understanding investment trends and the development of the Islamic capital market in the past few years in_order to understand the Islamic finance industry in the Islamic capital market inIndonesia. The Islamic capital market bridges Muslim investors with sharia/Islamic principles with clear information, without usury, speculation or gambling that is contrary to sharia/Islamic principles with proper contracts. In order to avoid the trend of investing without understanding the Islamic capital market as a Muslim.